Characterization of biosynthesized chitosan nanoparticles from Penaeus vannamei for the immobilization of P. vannamei protease: An eco-friendly nanobiocatalyst. (29th December 2017) - Shojaei, Fozieh; Homaei, Ahmad; Taherizadeh, Mohammad Reza; Kamrani, Ehsan
ABSTRACT: Nanomaterials are being applied due to their excellent characteristics, such as the high surface area-to-volume ratio, excellent physicochemical properties, and biological compatibility. Chitosan is an amino polysaccharide and a versatile, second-most abundant natural polymer. In this presented work, chitosan was purified from Penaeus vannamei from the Persian Gulf and the homogeneity level was used a combination of three procedures: deproteinization, demineralization, and deacetylation. Chitosan nanoparticles were synthesized by the ionization gelation technique. P. vannamei protease immobilized on the surface of the positively charged chitosan nanoparticles through ionic or electrostatic interaction. The immobilized enzyme exhibited better tolerance to variations in the medium pH and temperature, enhanced pH and temperature stability, improved storage stability, and good reusability compared with the free enzyme. The Michaelis–Menten kinetic constant (Km ), the maximum reaction velocity (Vmax ), and the catalytic efficiency (kcat ) for native P. vannamei protease were 2.5 µM, 87 µM. min −1, and 132 min −1, respectively, whereas for immobilized enzyme, Km, Vmax, and kcat values were 2.7 µM, 83 µM. min −1, and 128 min −1, respectively. The effect of both soluble and immobilized P. vannamei protease on the clarification of orange juice was also analysed.